De-Stalinising Eastern Europe
XIV, 262 p.
Keywords: This unique volume examines how and to what extent former victims of Stalinist terror from across the Soviet Union and Eastern Europe were received, reintegrated and rehabilitated following the mass releases from prisons and labour camps which came in the wake of Stalin's death in 1953 and Khrushchev's reforms in the subsequent decade.